2018
DOI: 10.1002/jlb.5ri0917-380rr
|View full text |Cite
|
Sign up to set email alerts
|

BET proteins in abnormal metabolism, inflammation, and the breast cancer microenvironment

Abstract: Obesity and its associated pathology Type 2 diabetes are two chronic metabolic and inflammatory diseases that promote breast cancer progression, metastasis, and poor outcomes. Emerging critical opinion considers unresolved inflammation and abnormal metabolism separately from obesity; settings where they do not co-occur can inform disease mechanism. In breast cancer, the tumor microenvironment is often infiltrated with T effector and T regulatory cells programmed by metabolic signaling. The pathways by which tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 158 publications
0
35
0
Order By: Relevance
“…As a chronic disease, T2D may cause inflammatory response in different organs or tissues (34). Increasing studies report the critical role of BRD4 in the regulation of inflammatory response, suggesting that BRD4 might be implicated in the pathology of diabetes (35,36).…”
Section: Disscusionmentioning
confidence: 99%
“…As a chronic disease, T2D may cause inflammatory response in different organs or tissues (34). Increasing studies report the critical role of BRD4 in the regulation of inflammatory response, suggesting that BRD4 might be implicated in the pathology of diabetes (35,36).…”
Section: Disscusionmentioning
confidence: 99%
“…BETs inhibition was initially shown to be highly effective in blocking transcription programs of inflammation 28 and oncogenic proliferation 29 . The importance of BET biology was then extended to stem cell differentiation, hematopoiesis, synaptic plasticity 12 , and recently, also adipogenesis 10,30 . Most recently, BRD4 was found to regulate intra-nuclear/cellular processes as well, such as chromatin architectural remodeling 31 and autophagy 11 .…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 has been shown to play a master role in broad cellular processes ranging from proliferation to differentiation 10 to autophagy 11 . Curiously, whether BETs are directly involved in cholesterol homeostasis remained unclear 12 . Relevant to this question, recent studies identified a crucial role of BRD4 in adipogenesis 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, the molecular signaling events that occur within the TME function to promote tumor progression and enable cancer cells to acquire phenotypic properties such as enhanced invasion and migration that are critical to the development of cancer metastasis. In support of this, recent data suggests a direct role for BRD4 in the epigenetic regulation of gene expression in both cancer cells and non-neoplastic cells present in the TME that promotes tumorigenesis [15, 34]. …”
Section: Introductionmentioning
confidence: 93%
“…Jagged1 is a Notch ligand and upon binding of Jagged1 to the Notch receptor, Notch is cleaved and translocates to the nucleus where it binds to CBF1, Suppressor of Hairless, Lag-1 (CSL) and Coenzyme A (CoAs) and activates the expression of transcription factors that are vital in EMT, such as Snail and Slug [32]. Studies have shown that BRD4 promotes the migratory properties of breast cancer cell lines through Notch1-induced signaling [15, 33]. Interestingly, studies have demonstrated that the pro-inflammatory cytokine IL-6 increases BRD4 enrichment at the proximal portion of the Jagged1 promoter region, supporting the idea that tumor-associated inflammatory mediators may alter the epigenetic ‘reading’ functions of BRD4 in cancer cells.…”
Section: Introductionmentioning
confidence: 99%